2016
DOI: 10.1371/journal.pone.0168349
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Left Ventricular Remodeling after a Myocardial Infarction: Role of Myocardial Deformation: A Systematic Review and Meta-Analysis

Abstract: AimsLeft ventricular (LV) adverse or reverse remodeling after ST-segment elevation myocardial infarction (MI) is the best outcome to assess the benefit of revascularization. Speckle tracking echocardiography (STE) may accurately identify early deformation impairment, while also being predictive of LV remodeling during follow-up. This systematic analysis aimed to provide a comprehensive review of current findings on STE as a predictor of LV remodeling after MI.MethodsPubMed databases were searched through Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 44 publications
2
31
0
7
Order By: Relevance
“…On the other hand, GLS rate showed a slight improvement only in the usual care group in our study. Similarly, the most important parameter in the prediction of ventricular remodeling, GLS, tended to improve over time, but more pronounced in the usual care group . A recent explorative non‐randomized study found no beneficial effects on left ventricular dimension and function in post‐AMI patients (including GLS and LV twist) .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…On the other hand, GLS rate showed a slight improvement only in the usual care group in our study. Similarly, the most important parameter in the prediction of ventricular remodeling, GLS, tended to improve over time, but more pronounced in the usual care group . A recent explorative non‐randomized study found no beneficial effects on left ventricular dimension and function in post‐AMI patients (including GLS and LV twist) .…”
Section: Discussionmentioning
confidence: 97%
“…It is more sensitive for the detection of subclinical LV changes as compared to standard LV ejection fraction (LVEF) measurement . The best evaluated parameter, global longitudinal strain (GLS) is superior to LVEF in the prediction of prognosis and cardiac remodeling after AMI . Among others, cardiac β‐adrenergic receptor (β‐AR) signal dysregulation represents a hallmark abnormality potentially leading to LV remodeling post‐AMI and progression to heart failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports, both experimental and clinical, have demonstrated usefulness of systolic deformation parameters for the assessment of viability and predicting recovery of regional function after myocardial infarction (Zhang et al ., ; Migrino et al ., ; Vartdal et al ., ; Lipiec et al ., ; Szymczyk et al ., ). Peak SLS measurements obtained by speckle tracking echocardiography have also been shown to be predictive of left ventricular remodelling after myocardial infarction (Huttin et al ., ). In our study, we confirmed most of these observations.…”
Section: Discussionmentioning
confidence: 97%
“…Novel functional strategies using assessment of myocardial deformation with speckle tracking echocardiography can be used readily at the bedside. Several studies have suggested that assessment of peak systolic longitudinal strain after revascularization in patients with acute myocardial infarction can be used for predicting global improvement in LVEF (32). …”
Section: Assessment For Myocardial Perfusion and Viabilitymentioning
confidence: 99%